Administration of turmeric kombucha ameliorates lipopolysaccharide-induced sepsis by attenuating inflammation and modulating gut microbiota - Su, Jingqian; Tan, Qingqing; Wu, Shun; Zhou, Fen; Xu, Chen; Zhao, Heng; Lin, Congfan; Deng, Xiaohui; Xie, Lian; Lin, Xinrui; Ye, Hui; Yang, Minhe (Frontiers in Microbiology, 2024)
Our research team previously reported the immunomodulatory effects of kombucha fermentation liquid. This study investigated the protective effects of turmeric kombucha (TK) against lipopolysaccharide (LPS)-induced sepsis and its impact on the intestinal microbiota of mice. A turmeric culture medium without kombucha served as the control (TW). Non-targeted metabolomics analysis was employed to analyze the compositional differences between TK and TW. Qualitative analysis identified 590 unique metabolites that distinguished TK from TW. TK improved survival from 40% to 90%, enhanced thermoregulation, and reduced pro-inflammatory factor expression and inflammatory cell infiltration in the lung tissue, suppressing the NF-κB signaling pathway. TK also altered the microbiome, promoting Allobaculum growth. Our findings shed light on the protective effects and underlying mechanisms of TK in mitigating LPS-induced sepsis, highlighting TK as a promising anti-inflammatory agent and revealing new functions of kombucha prepared through traditional fermentation methods.